The study of the factors influencing consumers’ satisfaction in Shopee - Juan, Phoon Hui; JunQiao, Qiu; Selvam, Renusha; Dandamudi, Sairaja (AIBPM Publisher, 2023)
In recent years, online shopping has become a culture to fulfill consumers’ needs and wants. E-commerce can be a platform that provides people a chance to develop new business models, although they may experience a certain amount of risk associated with their purchase. Therefore, Shopee has become one of the leading e-commerce platforms in Malaysia. The purpose of this study is to investigate the factors that influence consumers' satisfaction with Shopee for online purchases. There are five factors that were assessed which included product quality, E-service quality, security, price and convenience. An electronic survey questionnaire was used to collect data. A total of 100 Shopee users from Malaysia responded to the survey. The findings revealed that the consumers’ satisfaction in Shopee had further accelerated due to the product quality, E-service quality and convenience. Meanwhile, security and price did not significantly influence consumers' satisfaction in Shopee. This study provides Shopee with valuable insights and guidance on consumers’ perception of Shopee, leading to improved customer satisfaction.